2022
DOI: 10.3390/app12115297
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Cosmic-Ray-Induced Atmospheric Ionization and Radiation at Commercial Aviation Flight Altitudes

Abstract: The main source of the ionization of the Earth’s atmosphere is the cosmic radiation that depends on solar activity as well as geomagnetic activity. Galactic cosmic rays constitute a permanent radiation background and contribute significantly to the radiation exposure inside the atmosphere. In this work, the cosmic-ray-induced ionization of the Earth’s atmosphere, due to both solar and galactic cosmic radiation during the recent solar cycles 23 (1996–2008) and 24 (2008–2019), was studied globally. Estimations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Figure 6 presents time profiles of the annual values of CRII rate and ambient dose equivalent rate for the same period of time (year 1996 to 2019) for the three typical FLs and for four different geomagnetic cut-off rigidities (0.1 GV, 3.1 GV, 8.5 GV and 14.9 GV). It is observed that both CRII rate (blue lines, left axis) and ambient dose equivalent rate (red lines, right axis) follow an 11-year modulation, at all the locations, the same way the Galactic Cosmic Ray intensity does (Makrantoni et al 2021(Makrantoni et al , 2022Tezari et al 2022;Mavromichalaki et al 1995), as the intensity of the cosmic radiation directly affects the radiation exposure of the aircrew.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Figure 6 presents time profiles of the annual values of CRII rate and ambient dose equivalent rate for the same period of time (year 1996 to 2019) for the three typical FLs and for four different geomagnetic cut-off rigidities (0.1 GV, 3.1 GV, 8.5 GV and 14.9 GV). It is observed that both CRII rate (blue lines, left axis) and ambient dose equivalent rate (red lines, right axis) follow an 11-year modulation, at all the locations, the same way the Galactic Cosmic Ray intensity does (Makrantoni et al 2021(Makrantoni et al , 2022Tezari et al 2022;Mavromichalaki et al 1995), as the intensity of the cosmic radiation directly affects the radiation exposure of the aircrew.…”
Section: Resultsmentioning
confidence: 93%
“…This fact is due to the CRII following the cosmic ray intensity behavior with which it is positively correlated, while it is negatively correlated with the solar activity. This means that the greater the solar activity, the lower the intensity of the CRII and vice versa Gleeson and Axford 1968;Mavromichalaki et al 1998;Makrantoni et al 2013Makrantoni et al , 2021Makrantoni et al , 2022.…”
Section: Resultsmentioning
confidence: 99%
“…Many models have been developed to compute the ionization caused by cosmic rays in the atmosphere, such as PLANETOCOSMICS [18], CRAC:CRII [19], and others [20,21]. Recently, computations of the ionization rate were performed for the entire surface of the Earth at various altitudes during quiet periods and also for SEP events [22,23]. In addition to contributing to atmospheric ionization, cosmic rays lead to radiation exposure in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…These extreme events may be particularly harmful to technological infrastructure systems, both space-borne and terrestrial [16][17][18]. They may also pose a danger to human health, as far as astronauts and possibly aircrews are concerned [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%